Cognitive, Motor, and Behavioral Function in PKU - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Measures of cognitive, frontal lobe (executive), behavioral and motor function were administered to 18 children (aged 12-101 months) with phenylketonuria followed at the University of Rochester School of Medicine, NY.